Reversible selective embedding for DICOM image security and integrity using visual cryptography. (15th June 2021) - Paikaray, Bijay Kumar; Swain, Debabala; Chakravarty, Sujata
Information security has been one of the biggest challenges in the era of telemedicine applications. To protect the patient's private records in medical images, several traditional methods are used. One of them is hiding the sensitive part of the image by embedding a different message into it. The data embedding can be done using methods like reversible data hiding (RDH) or reversible watermarking in the region of interest (ROI) of the original medical images. For ensuring the authenticity and integrity of the received medical image, an innovative data embedding technique is proposed in this paper. The proposed technique chooses selective blocks from the ROI based on the smoothness function and the region of non-interest (RONI) is embedded into ROI using some reversible operations. The proposed technique is an application of visual cryptography where the embedded region cannot be visually detected by an attacker. The experimental results prove the reversibility and the efficiency of the proposed approach.